HUBUNGAN FAKTOR DEMOGRAFI DAN DUKUNGAN SOSIAL DENGAN KUALITAS HIDUP PASIEN KUSTA MULTIBASILER PASCA MULTY DRUG THERAPY (STUDI KASUS DI RS KUSTA SUMBERGLAGAH MOJOKERTO) - Denyk Eko Meiningtyas; Arief Hargono (The Indonesian Journal of Public Health, 2018)
Leprosy is a complex condition involving the physical health and quality of life of the patient. Measurement of quality of life aims to assess health and health care obtained by patients. Quality of life is closely related to the stigma. Stigma in leprosy patients can decrease the quality of life of leprosy patients. The purpose of this study is to analyze quality of life leprosy patients with post-Multy Drug Therapy at Sumberglagah leprosy hospital Mojokerto Regency. This research was an observational research, using cross sectional research design. A sample of 80 subjects, was taken by consecutive sampling. Secondary data in the form of list of leprosy patients and primary data was obtained by questionnaires. Data was analysed by Chi Square. The result showed that the distribution of leprosy patients was mostly in the productive age group of 49 people (61,3%), male gender 45 people (56,3%), low educated 58 people (72,5%), and had high social support 52 people (65%). Age factor (p=0,035), education (p=0,003) and social support (p=0,009) have positif correlation with quality of life of leprosy patients. The sex factor (p=0.623) has no relationship with quality of life of leprosy patients. The conclusions of this study were age, education, and social support factors has relationship with the quality of life of patients with post-Multy Drug Therapy mutlibacillary leprosy in Sumberglagah Mojokerto Hospital. Efforts to hold discussion groups for leprosy patients, increase the leprosy confidence of lepers to be active and productive, and conduct health promotion with socialization is expected to improve the quality of life of leprosy patients.